ANALISIS EFEKTIVITAS DAN EFISIENSI PEROLEHAN PAJAK DAN RETRIBUSI HOTEL DAN RESTORAN SEBELUM DAN SAAT COVID-19 PADA KOTA/ KABUPATEN DI PROVINSI BALI - Anak Agung Ngurah Lanang Nila Dawan; Komang Agus Rudi Indra Laksmana; Komang Asri Pratiwi (Nusantara Hasana Journal, 2022)
Covid-19 hit the tourism sector, especially in the province of Bali, where the source of the original regional income is mostly from the tourism sector. Therefore, areas that rely on tourism will be directly affected. In this study to determine whether there are differences and how the level of Effectiveness and Efficiency of hotel and restaurant taxes and levies during the period from 2017 to 2020. The method used in this study uses quantitative data. The calculation of the results of the effectiveness and efficiency values ​​is based on a comparison with the standard criteria for the effectiveness ratio and efficiency ratio, then the next stage is the average before and when Covid-19 is carried out a different test or better known as the T Test which is one of various methods. The test used to assess the effectiveness of the treatment was marked by the difference between the average before and the average after. The results of the research obtained, it is said that every district/city before and during Covid-19 shows the results that Jembrana Regency is rated as effective balanced towards effective but less efficient towards balanced efficiency, Tabanan Regency is effective towards less effective but efficient towards balanced efficiency, Badung Regency is equally less effective but efficient towards balanced efficiency, Gianyar Regency effective towards less effective but equally efficient, Klungkung Regency equally effective but efficient towards balanced efficiency, Bangli Regency equally less effective but balanced efficiency towards less efficient, Karangasem Regency equally equally less effective but efficient towards balanced efficiency, Buleleng Regency effective towards less effective but equally less efficient, and Denpasar City effective towards less effective but equally less efficient.